2018
DOI: 10.1002/prop.201800014
|View full text |Cite
|
Sign up to set email alerts
|

Supergravity in the Group‐Geometric Framework: A Primer

Abstract: We review the group‐geometric approach to supergravity theories, in the perspective of recent developments and applications. Usual diffeomorphisms, gauge symmetries and supersymmetries are unified as superdiffeomorphisms in a supergroup manifold. Integration on supermanifolds is briefly revisited, and used as a tool to provide a bridge between component and superspace actions. As an illustration of the constructive techniques, the cases of d=3,4 off‐shell supergravities and d=5 Chern‐Simons supergravity are di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 92 publications
2
12
0
Order By: Relevance
“…This framework is well suited also to the case of p-form fields coupled to (super)gravity, and a group-geometric approach has been developed since the late 70's based on free differential algebras (FDA's) [1]- [8] (for a recent review see for ex. [9] ). In the 80's a form-Hamiltonian formalism was proposed in a series of papers [10]- [14], where momenta π conjugated to basic p-form fields φ are defined as "derivatives" of the d-form Lagrangian with respect to the "velocities" dφ, and the d-form Hamiltonian is defined as H = (dφ)π−L.…”
Section: Introductionmentioning
confidence: 99%
“…This framework is well suited also to the case of p-form fields coupled to (super)gravity, and a group-geometric approach has been developed since the late 70's based on free differential algebras (FDA's) [1]- [8] (for a recent review see for ex. [9] ). In the 80's a form-Hamiltonian formalism was proposed in a series of papers [10]- [14], where momenta π conjugated to basic p-form fields φ are defined as "derivatives" of the d-form Lagrangian with respect to the "velocities" dφ, and the d-form Hamiltonian is defined as H = (dφ)π−L.…”
Section: Introductionmentioning
confidence: 99%
“…These theories possess local supersymmetry and, if the superalgebra contains the Lorentz or (A)dS algebra, represented by a Lorentz connection and a vielbein, they also include gravity. The gauge fields associated with the SUSY generators are spin 3/2 fermions (gravitini), while the internal symmetry has standard spin 1 gauge fields [15,16]. These CS supergravity theories are covariant under general coordinate transformations, they do not exhibit matching SUSY pairs and, although they are topological in a certain sense, they describe propagating degrees of freedom [1].…”
Section: Standard and Cs Supergravitiesmentioning
confidence: 99%
“…The parametrizations (28a)-(28g) we have obtained above allow to derive the supersymmetry transformations in a direct way. Indeed, in the geometric framework we have adopted, the transformations on space-time are given by (see [23,24] and [25] for details):…”
Section: Supersymmetry Transformation Laws Obtained Within the Geometmentioning
confidence: 99%
“…More recently, in [22] the authors constructed the N = 1 and N = 2, D = 4 supergravity theories with negative cosmological constant in the presence of a non-trivial boundary in a geometric framework (extending to superspace the geometric approach of [11][12][13][14][15]): Precisely, they generalized the so-called rheonomic (geometric) approach to supergravity [23] (see also [24,25] for recent reviews of this framework) in the presence of a non-trivial boundary and they added proper boundary terms to the Lagrangian in order to restore the supersymmetry invariance of the theory. In particular, the authors found that the supersymmetry invariance of the full Lagrangian (understood as bulk plus boundary contributions) is recovered with the introduction of a supersymmetric extension of the Gauss-Bonnet term.…”
Section: Introductionmentioning
confidence: 99%